Deoxygenation of model biofuel compounds over CsNaX zeolite catalyst - Danuthai, Tanate; Peralta, Maria A.; Sooknoi, Tawan; Osuwan, Somchai; Lobban, Lance L.; Mallinson, Richard G.; Resasco, Daniel E. (My University, 2008)
The deoxygenation of methyl octanoate and benzaldehyde over CsNaX zeolite catalyst has been investigated as a model for reactions for production of hydrocarbon fuels from bio-oxygenates. The CsNaX zeolite used in the study was prepared by ion exchange of NaX with a CsNO3/CsOH solution to a 50% exchange level. The decarbonylation activity, selectivity, and stability of the CsNaX catalyst were enhanced when methanol was co-fed for the reaction of methyl octanoate. TPD studies suggest that methyl octanoate first decomposes to an octanoate-like species. The decomposition of such species leads to the formation of heptenes and hexenes as major products. Octenes and hydrogenated products are formed in lesser amounts via hydrogenation / hydrogenolysis using hydrogen produced on the surface from methanol decomposition, but not from gas phase H2.